Comparative analysis of plant transient expression vectors for targeted N-glycosylation - Eidenberger, Lukas; Eminger, Florian; Castilho, Alexandra; Steinkellner, Herta (Frontiers in Bioengineering and Biotechnology, 2022)
While plant-based transient expression systems have demonstrated their potency to rapidly express economically feasible quantities of complex human proteins, less is known about their compatibility with posttranslational modification control. Here we investigated three commonly used transient expression vectors, pEAQ, magnICON and pTra for their capability to express a multi-component protein with controlled and modified N-glycosylation. Cetuximab (Cx), a therapeutic IgG1 monoclonal antibody, which carries next to the conserved Fc an additional N-glycosylation site (GS) in the Fab-domain, was used as model. While pEAQ and pTra produce fully assembled Cx at similar levels in N. benthamiana, the yield of magnICON-Cx was twice as high. When expressed in wild type plants, both Cx-GSs exhibited typical plant N-glycans decorated with plant-specific xylose and fucose. Likewise, Cx generated in the glycoengineered ΔXTFT line carried mainly complex N-glycans lacking plant specific residues. Exposure to different engineering settings (encompassing stable lines and transient approaches) towards human galactosylation and sialylation resulted in Cx carrying targeted N-glycans at similar quantities using all three expression vectors. Collectively, our results exhibit the universal application of plant-based glycoengineering, thereby increasing the attractivity of the ambitious expression platform.